The Experiences of Māori Occupational Therapists: Navigating Cultural Safety and Cultural Load in the Mental Health Sector of Aotearoa - Brown Tawhiri, Georgia (Auckland University of Technology, 2025)
There has been a shift towards cultural competence and cultural safety in Aotearoa in the last 30 years, and the Māori health workforce has played a fundamental role in the development and implementation of these concepts (Ramsden, 1993; Hunter & Cook, 2020; Tofi et al., 2023). The knowledge, skillset and experience of cultural values, practices and the lived reality of being Māori in Aotearoa is an attribute that the Māori health workforce possess (Wilson et al., 2022; Te Aka Whaiora, 2024). This skillset being highly sought after by services and organisations has created a demand and pressure on the low number of Māori working in the mental health sector, in particular Māori occupational therapists. Māori occupational therapists are shouldering cultural load and culturally unsafe situations in attempts to ensure tangata whaiora Māori receive the clinically and culturally appropriate care they need and are entitled to. This research explores the experiences of Māori occupational therapists working in the mental health sector in Aotearoa and how they navigate cultural safety and cultural load within this space. Kaupapa Māori methodology was the foundational underpinning of this research, with the interface and coming together of narrative inquiry. The Whakaāria analysis method was used to identify and interpret huahuatau (themes) within the research through the use of whakataukī and whakatauākī. Racism, cultural clinical workload, cultural obligations, internal psychological battles and protective factors contributing to cultural safety, were significant areas of interest in the findings. These huahuatau then informed a discussion around how to best support and mitigate culturally unsafe experiences for Māori occupational therapists in the mental health sector in Aotearoa.